Pengaruh Zakat dalam Mengurangi Kemiskinan Di Kota Pekalongan Pasca Pandemi - S saebani; cholisa Rosanti (Neraca, 2022)
This study discusses several factors that influence poverty alleviation in the city of Pekalongan, as a social institution Lazismu is needed by the community to alleviate poverty in the city of Pekalongan. The data source used is the primary data source with a population of 90 people in the city of Pekalongan, a sample of people who have received post-pandemic lazismu assistance funds. Simultaneously the variables in this study affect poverty alleviation in the city of Pekalongan. The analytical tool used in analyzing the problem is SPSS 16. Keywords: Zakat, poverty, Lazismu, Pandemic